Shallow-water bryozoans collected during R.V. Meteor expedition 5/2 “MINDIK” from the Bab-el-Mandeb Strait and Gulf of Aden, along the coasts of Djibouti and Yemen - Martha, Silviu O.; Scholz, Joachim (Zootaxa, 2025)
This study provides a comprehensive taxonomic account of bryozoans from the Gulf of Aden and the Bab-el-Mandeb Strait, a biogeographically significant region at the confluence of the Red Sea and the northwestern Indian Ocean that remains underexplored. Based on material collected during R.V. Meteor expedition 5/2 “MINDIK” along the coasts of Djibouti and Yemen, we identify and document 20 bryozoan taxa, comprising 19 cheilostome species and one cyclostome species. New regional occurrences are reported for Characodoma protrusum, Labioporella crenulata, Lagenipora perplexa, Onychocella subsymmetrica, Porina australiensis, and Smittipora harmeriana, significantly extending their known distributions into the northwestern Indian Ocean. Three previously described species, Anoteropora latirostris, Iodictyum magniavicularis, and Reussirella indica, are re-evaluated, with revisions to their diagnostic features. Five species are described as new to science: Adeona odontoti sp. nov., Characodoma babelmandebi sp. nov., Mucropetraliella marielou sp. nov., Parasmittina karlae sp. nov., and Plesiocleidochasma dorothyjohnella sp. nov. In addition, Thalamoporella annmargretae nom. nov. is introduced as a substitute name for a junior homonym. Nevianipora sp. represents the first documented cyclostome bryozoan from the Gulf of Aden. This work underscores the underestimated diversity and biogeographic complexity of bryozoan assemblages in the Gulf of Aden and Bab-el-Mandeb Strait, providing a critical baseline for future biodiversity, paleobiogeographic, and evolutionary studies in this poorly investigated marine region.